The Indian marine flsheries resources scenario present and future - James, P S B R (Indian Journal of Fisheries, 2011)
In the marine; fisheries sector of India, the emphasis until recently was on development and increasedexploitation which lead to intense fishing activity in the 0-50 m depth zone resulting in near optimalexploitation of most stocks inhabiting this region. "Die data cii fisheiy and biology ccdlected over a numberof years on a large number of exploited species from the exploited grounds of 0-50 m depth zone show thatthere is no scope for increasing production from this region and that the emphasis should be given toeffectively manage the resources to ensure sustained returns. In the unexploited grounds beyond 50 m depththe potential yield is of considerable magnitude (1.7 million tonnes) and, therefore, the future oi marinefisheries depends largely on continuing the present level of exploitation in the inshore waters, exploitationof resources from the relatively deep seas, and researches aimed at stock assessment, particularly assessmentof mixed or multispecies fisheries, which will help in formulation (d policies for resource management inthe entire exclusive economic zone oi India.